DEVELOPING STUDENTS SPEAKING SKILLS THROUGH TASK BASED METHODS. TEACHING SPEAKING TO EFL LEARNERS - Abdurasulova Maftuna; Yuldasheva S.F. (Journal of new century innovations, 2022)
Abstract: Speaking is an essential component of teaching and learning a second language. Speaking should be taught so that students can communicate in real-world settings, not just by having them repeat or remember monologues. In order to avoid forcing students to speak and putting them in a state of intense anxiety, teachers' responses to what students think and believe are crucial. Instead, we encourage students to use any language they choose when participating in oral tasks where they are given a task and must complete it. Teachers should be able to set up scenarios where pupils are given worthwhile assignments that will advance their speaking skills. When students work in groups with their peers to finish a task, this can be realized. Task- Based approach is the alternate to solve the problem where learning is developed through performing a series of activities as steps towards successful task realization.